Progresses in interventional cardiology: focus on patent foramen ovale, coronary intervention, antithrombotic pharmacology and more. (February 2013) - Capodanno, Davide; Capranzano, Piera
Transcatheter Cardiovascular Therapeutics 2012 Miami, FL, USA, 22–26 October 2012 Transcatheter Cardiovascular Therapeutics (TCT) is the largest meeting in the USA in the field of interventional and vascular medicine. Every year, the symposium showcases numerous sessions dedicated to late-breaking clinical trials, a unique educational window for evidence-based medicine to guide management of patients with atherosclerosis and structural heart disease. This year, late-breaking trials at TCT mainly focused on patent foramen ovale closure, coronary intervention, interventional pharmacology and transcatheter aortic valve implantation. In this article, for the sake of the busy reader who could not attend the meeting, we highlight a selection of the trials firstly presented in the 2012 edition of TCT.